Failure to Rescue in Geriatric Trauma: The Impact of Any Complication Increases with Age and Injury Severity in Elderly Trauma Patients. Issue 11 (November 2021) - Stonko, David P.; Etchill, Eric W.; Giuliano, Katherine A.; DiBrito, Sandra R.; Eisenson, Daniel; Heinrichs, Trevor; Morrison, Jonathan J.; Haut, Elliott R.; Kent, Alistair J.
Introduction: The interaction of increasing age, Injury Severity Score (ISS), and complications is not well described in geriatric trauma patients. We hypothesized that failure to rescue rate from any complication worsens with age and injury severity. Methods: The National Trauma Data Bank (NTDB) was queried for injured patients aged 65 years or older from January 1, 2013 through December 31, 2016. Demographics and injury characteristics were used to compare groups. Mortality rates were calculated across subgroups of age and ISS, and captured with heatmaps. Multivariable logistic regression was performed to identify independent predictors of mortality. Results: 614, 496 geriatric trauma patients were included; 151, 880 (24.7%) experienced a complication. Those with complications tended to be older, female, non-white, have non-blunt mechanism, higher ISS, and hypotension on arrival. Overall mortality was highest (19%) in the oldest (≥86 years old) and most severely injured (ISS ≥ 25) patients, with constant age increasing across each ISS group was associated with a 157% increase in overall mortality ( P < .001, 95% CI: 148-167%). Holding ISS stable, increasing age group was associated with a 48% increase in overall mortality ( P < .001, 95% CI: 44-52%). After controlling for standard demographic variables at presentation, the existence of any complication was an independent predictor of overall mortality in geriatric patients (OR: 2.3; 95% CI: 2.2-2.4). Conclusions: Any complication was an independent risk factor for mortality, and scaled with increasing age and ISS in geriatric patients. Differences in failure to rescue between populations may reflect critical differences in physiologic vulnerability that could represent targets for interventions.